Kinek használ az évvesztés? Iskolakezdési kor és tanulói teljesítmények Magyarországon - Szilvia Hámori; János Köllő (Hungarian Academy of Sciences, Institute of Economics, 2010)
– This paper estimates the effect of school starting age on academic performance using the 2006 "National Assessment of Basic Competencies" (NABC), focusing on disadvantaged and non-disadvantaged children. The instrumental variable estimates of the school starting age imply that those who start school at the age of seven do better on competency tests than those children who start school at the age of six. This benefit is substantially larger for disadvantaged children than their non-disadvantaged counterparts. However, the benefit of later enrolment diminishes as children - both disadvantaged and non-disadvantaged - progress through school.
Keywords: I21; I28; J24; 330; education; student test scores; enrolment age; identification; Schüler; Altersgruppe; Bildungschancen; Bildungsertrag; Ungarn